Introduction of the OsGERLP Gene into Potato cv. IPB CP3 to Develop Aluminum Stress-Tolerant Potato Lines - Mahfudhah, Farah; Tjahjoleksono, Aris; Miftahudin, M. (HAYATI Journal of Biosciences, 2026)
The OsGERLP gene is an aluminum (Al) stress tolerance gene. Potato cv. IPB CP3 is a horticultural crop that has not been proven to be tolerant to Al; therefore, enhancing its tolerance through genetic transformation is necessary. This research aims to obtain transgenic potatoes cv. IPB CP3 contains the OsGERLP gene and is tolerant to Al stress. Experimental methods include transforming potatoes with the OsGERLP gene via Agrobacterium tumefaciens, transgene integration testing, in vitro assays of transgenic plants under low pH and Al stress, and analysis of transgene expression. The results showed that the transformation efficiency achieved was relatively high at 47.03%, with a regeneration efficiency of 42.19%. The transgenic clones had longer roots and more roots than the non-transgenic ones under aluminum stress. The transgenic clones GERLP2, GERLP3, and GERLP4 exhibited the greatest root growth enhancement under stress conditions and the highest OsGERLP gene expression levels. These clones have the potential to be developed into Al-tolerant potato varieties. Future research is required to evaluate aluminum stress tolerance, tuber yield performance, and transgene stability across the three clones under greenhouse and field conditions of the three clones.